The Stigma of Mental Illness - End of the Story? - Gaebel, Wolfgang; Rössler, Wulf; Sartorius, Norman (Springer International Publishing : Imprint: Springer, 2017)
This book makes a highly innovative contribution to overcoming the stigma and discrimination associated with mental illness - still the heaviest burden both for those afflicted and those caring for them. The scene is set by the presentation of different fundamental perspectives on the problem of stigma and discrimination by researchers, consumers, families, and human rights experts. Current knowledge and practice used in reducing stigma are then described, with information on the programmes adopted across the world and their utility, feasibility, and effectiveness. The core of the volume comprises descriptions of new approaches and innovative programmes specifically designed to overcome stigma and discrimination. In the closing part of the book, the editors - all respected experts in the field - summarize some of the most important evidence- and experience-based recommendations for future action to successfully rewrite the long and burdensome 'story' of mental illness stigma and discrimination.